Zihar dalam Surat Al-Mujadillah 1-4 Perspektif Tafsir Maqasid - Taaibah Ngaunillah Rohmatun; Mad Yahya; Siti Muliana (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Zihar was considered divorced in the Jahiliyya era. When Islam came precisely at the time of the Khaulah Binti Tsalabah event which was zihar, and she did not want to be separated from her husband, she complained to the Prophet Muhammad until Surah Al-Mujadillah verses 1-4 came down which states that if someone wants to be free from zihar then he must pay expiation. In this contemporary era, the implementation of zihar is not only for men to women but also women to men. This is because the interaction between husband and wife is very important in a relationship. Hence, the formulation of the problem in this study is how is the relationship between partners in building interaction between the two because both have an important role in the household. This research is qualitative and uses Abdul Mustaqim's maqasid interpretation analysis knife to find the maqasid of Al-Mujadillah verses 1-4. The maqasid of this verse are hifz nafs and hifz nasl by freeing slaves, hifz nafs by rushing successively, hifd nafs, hifz mal and hifd din by feeding 60 poor people. Besides that, there is a maqasid from the gender aspect of this verse, namely the importance of hearing women's voices and having to provide justice for women. In addition, there is the main maqasid related to the relationship between husband and wife in this verse, namely maintaining the relationship between husband and wife when there is a problem, it is the responsibility of both, not just one party.